Anadyoméni de Grigorios Xénopoulos - Gunnar De Boel (Cahiers Balkaniques)
Xenopoulos’ novel Anadyomeni presents a dense network of literary, philosophical and liturgical references to meals, which set the stage for the enactment of the discussion, in Plato’s Symposium, about immortality and giving one’s life for one’s lover, and of Empedocles’ idea of metempsychosis in the form of a plant.